Pengaplikasian Remote Audit dan Skeptisme Profesional Auditor dalam Mempertahankan Kualitas Audit pada Kantor Akuntan Publik di Surabaya - Suhartini, Dwi; Ayub Binsar Tamado (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This research aims to test the influence of Remote Audit and Professional Skepticism on Audit Quality. The object of the research is 117 partner auditors who work at the Public Accounting Office in the Surabaya region. Simple random sampling technique was used to determine the sample in this investigation by utilizing a probability sampling procedure. This research utilizes a quantitative research approach based on questionnaires sent to public accounting firms in Surabaya. Primary data is collected. Using WarpPLS Version 8.0 software, the data was analyzed using the Partial Least Square (PLS) approach. The results concluded that the more adequate the technology used by auditors in the implementation of remote auditing and the more questions about doubtful matters according to the auditor's observations, the audit quality will improve